ANALYSIS OF INSTITUTIONAL ADAPTIVE CAPACITY OF CENTRAL GOVERMENT IN DEVELOPING BIOENERGY - Aris Alberdi, Husnul
Indonesia has been trying to develop renewable energy to answer various existing problems related to low carbon development, energy security and climate change. One of the renewable energy sources in Indonesia that has great potential is bioenergy. The use of bioenergy in Indonesia has been carried out with various forms of energy sources such as biogas, biofuels, or various other forms of biomass. The targets that have been set by Indonesia as a form of contribution to efforts to reduce the impact of climate change are goals that are also being achieved in the development of bioenergy. The 23% renewable energy mix target by 2025 is a target that is not easy to achieve. The bioenergy management system is a complex system that involves not only social but also ecological or environmental systems. The energy management system can be seen as a socio-ecological system in the concept of adaptive governance that is subject to disruption, shock, and uncertainty. The literature on bioenergy management with an adaptive management perspective is still limited. In fact, adaptive governance can be one way to look at this condition. Adaptive governance does not only require good environmental management but also the role of actors who have adaptive capacities. Institutional adaptive capacity is a concept that looks at the elements / dimensions that exist within the institution that can encourage and create adaptive capacities for the actors involved or society in general. The concept of institutional adaptive capacity is a concept that will be used in this study. The object of this research is a formal institution or government that has an important role in energy management. This study aims to analyze the adaptive capacity of government institutions in the management and development of bioenergy in Indonesia. The research approach is a qualitative and quantitative approach. The research was conducted using the Adaptive capacity wheel (ACW) as a research framework. Data collection was carried out by using semi-structured interview methods, ACW questionnaires, and review of relevant documents. The nonprobability sampling method used for selecting respondents and key informants wasiv purposive sampling. Respondents and informants not only come from actors within government agencies but other actors such as the private sector (industry), academia, and associations that are relevant with predetermined criteria. The results showed that there was already an adaptive capacity of government institutions in the management and development of bioenergy, but there were still conditions or obstacles that could hinder it. The adaptive capacity of the institution is reflected in the variety of approaches and actors involved in bioenergy management; trust and openness of institutions; collaboration and accountability skills. However, there are still indicators that have not worked fully based on the concept of adaptive capacity such as legitimacy and equity in governance; mobilization of financial resources and increasing human resource capacity; information management and leadership influence, and monitoring and evaluation. Then using gap analysis, several actions / strategies can be formulated based on ideal conditions based on the theory and actual conditions based on the results of the analysis. Several strategies that can be implemented are strengthening the legal basis and regulation of bioenergy development to the level of legislation; clear division of roles and tasks for state-owned companies managing energy in bioenergy development; synchronization between government agencies through integrated information management and joint performance targets for bioenergy development.